2019
DOI: 10.1088/1755-1315/373/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor air quality parameters at Ambulatory Care Centre XYZ, Malaysia

Abstract: Indoor Air Quality (IAQ) problems are very important and necessary to consider in hospital and health care facilities such as in AMBULATORY CARE CENTRE XYZ (ACCXYZ), Malaysia. Majority complaints made by the hospital staff at level 1, state that they felt uncomfortable and suffering coldness due to very low temperature of centralizing air-conditioning especially during non-peak hours. Therefore, five parameters pointed to be measured based on the complaints from staff due to IAQ problems especially from Heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…In this study, the mean IAQ parameter values within the selected hospital OPDs were observed to be in accordance with the ICOP 2010 and ASHRAE standards, except for indoor air temperature and AV. This is similar to the findings of several studies conducted in Malaysian healthcare facilities [ 73 , 74 ], where similar parameters were substandard according to the standard limits. As observed in this study, occupants in naturally ventilated OPDs tended to open windows and doors, whereas those in mechanically ventilated OPDs tended not to.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the mean IAQ parameter values within the selected hospital OPDs were observed to be in accordance with the ICOP 2010 and ASHRAE standards, except for indoor air temperature and AV. This is similar to the findings of several studies conducted in Malaysian healthcare facilities [ 73 , 74 ], where similar parameters were substandard according to the standard limits. As observed in this study, occupants in naturally ventilated OPDs tended to open windows and doors, whereas those in mechanically ventilated OPDs tended not to.…”
Section: Discussionsupporting
confidence: 91%
“…Installing an HVAC system in a building is a critical factor in ensuring both comfort and excellent IAQ. It helps create a comfortable working environment and significantly impacts their work performance and health, facilitating productive activities [4]. Air-Conditioning (AC) systems usually ensure thermal comfort and maintain high IAQ by regulating temperature, humidity levels, and air cleanliness during distribution.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished through natural ventilation or mechanical ventilation. Most indoor air quality problems were caused by insufficient ventilation, which refers as follows: Heat, Ventilation, and Air Conditioning (HVAC) systems regulate three different parameters, including temperature, ventilation, and relative humidity (Aini et al, 2019). The use of HVAC system in any medical facility is crucial for several reasons.…”
Section: Introductionmentioning
confidence: 99%